PENGARUH KUALITAS PRODUK, PENETAPAN HARGA DAN DESAIN PRODUK TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR HONDA DI KECAMATAN REMBANG - Dwi Anggara Putra; Damayanti (JURNAL EKONOMI, 2023)
The purpose of this study was to prove the effect of product quality, pricing, and product design on purchasing decisions for Honda motorbikes in Rembang District. The population of this study is the people in the Rembang District who use Honda motorcycles. The sampling technique used convenience random sampling with a sample of 100 respondents. The data analysis technique uses multiple linear regression analysis with SPSS 24 tools in data processing. The results of the study prove that the variables of product quality, pricing, and product design have a significant positive effect on purchasing decisions for Honda motorcycles in Rembang District. The results of the determination test showed that the variables of product quality, pricing and product design were able to influence purchasing decisions by 82.9% while the remaining 17.1% were influenced by other variables outside of this study.